EFFORTS BY WOMEN TO BECOME FINANCIALLY INDEPENDENT THROUGH E-COMMERCE DURING COVID-19: A STUDY ON BANGLADESH PERSPECTIVE - Mimi, Afsana; Imran, Md. Ali; Mustafa, Jasia; Beg, Tahrima Haque; Rahman, Md. Sazidur (American Economic & Social Review, 2022)
This research investigates the efforts taken by the women for introducing themselves as financially independent through e-commerce from the perspective of Bangladesh. After the outbreak of COVID-19, women of Bangladesh suffered a lot in case of – loss of jobs, lower wages, lower educational support, lower access to information, and deterioration of mental health due to depression and anxiety. At this bad time, e-commerce has shown women a new way of survival and gained economic independence. This study is for evaluating how e-commerce becomes a strong tool for women’s economic independence during the period of this pandemic. Though there are some obstacles, e-commerce is opening the door to women’s success. Bangladesh is a developing country where most people think that the only duty of women is cooking and looking after children but e-commerce is giving the opportunity to the women to work at home and become financially independent. The policy recommendations for encouraging women in e-commerce and mitigating their challenges could be helpful for The Government of the People’s Republic of Bangladesh in making this sector more profitable. JEL Classification Codes: L81.